Lmod2piggyBac mutant mice exhibit dilated cardiomyopathy. Issue 1 (December 2016) - Li, Shuang; Mo, Kaiqi; Tian, Hong; Chu, Chen; Sun, Shuna; Tian, Lei; Ding, Sheng; Li, Tong-ruei; Wu, Xiaohui; Liu, Fang; Zhang, Zhen; Xu, Tian; et al.
Abstract Background Leiomodin proteins, Lmod1, Lmod2 and Lmod3, are key regulators of the thin filament length in muscles. WhileLmod1 is specifically expressed in smooth muscles, bothLmod2 andLmod3 are expressed in striated muscles including both cardiac and skeletal muscles. We and others have previously shown thatLmod3 mainly function in skeletal muscles and the mutant mice display disorganized sarcomere. Lmod2 protein has been found to act as an actin filament nucleator in both cell-free assays and in cultured rat and chicken cardiomyocytes. Results To better understand the function ofLmod2 in vivo, we have identified and characterized apiggyBac (PB ) insertional mouse mutant. Our analysis revealed that thePB transposon inserts in the first exon of theLmod2 gene and severely disrupts its expression. We found thatLmod2 PB/PB mice exhibit typical dilated cardiomyopathy (DCM) with ventricular arrhythmias and postnatal lethality. Electron microscope reveals that theLmod2 PB/PB hearts carry disordered sarcomere, disarrayed thin filaments, and distorted intercalated discs (ICDs). Those ICDs display not only decreased convolutions, but also reduced electron-dense staining, indicating less ICDs component proteins inLmod2 PB/PB hearts. Consistent with the phenotype, the expression of the ICD component genes, β-catenin and Connexin43, are down-regulated. Conclusions Taken together, our data reveal thatLmod2 is required in heart thin filaments for integrity of sarcomere and ICD and deficient mice exhibit DCM with ventricular arrhythmias and postnatal lethality. TheLmod2 PB/PB mutant offers a valuable resource for interrogation of pathogenesis and development of therapeutics for DCM.